Construction Of 100 Meters Short Distance Test In Penjaskesrek Student FKIP Islamic University Of Riau - Nova Risma; Kamarudin Kamarudin; Raffly Henjilito (Universitas PGRI Palembang, 2021)
This study aims to develop or modify the form of a test kit for short distance running 100 meters. The components that are repaired are only in the process of running from the start to the finish line. Usually a test run uses only the best time taken by the timer, then makes minor improvements according to the latest IAAF regulations. This research method uses research and development methods or research and development. The validation of the research and development instrument used content validation by several experts (expert judgment) which made one test and measurement expert and two athletic sports experts. Based on the results of the analysis of the expert test evaluation of the 100 meter short distance running instrument, it is declared valid and reliable, so that it can be used as research material for students of Penjaskesrek, Riau Islamic University.